Dynamic expression of Notch signaling genes in neural stem/progenitor cells - Hiromi eShimojo; Toshiyuki eOhtsuka; Ryoichiro eKageyama (Frontiers in Neuroscience, 2011)
In neural stem/progenitor cells, expression of the Notch effector Hes1, a transcriptional repressor, oscillates with a period of 2-3 hours by negative feedback, and Hes1 oscillations induce the oscillatory expression of the proneural gene Neurogenin2 (Ngn2) and the Notch ligand gene Delta-like1 (Dll1). Dll1 oscillation leads to the mutual activation of Notch signaling between neighboring cells, thereby maintaining a group of cells in the undifferentiated state. Not all cells express Hes1 in an oscillatory manner: cells in boundary regions such as the isthmus express Hes1 in a sustained manner, and these cells are rather dormant with regard to proliferation and differentiation. Thus, Hes1 allows cell proliferation and differentiation when its expression oscillates but induces dormancy when its expression is sustained. After Hes1 expression is repressed, Ngn2 is expressed in a sustained manner, promoting neuronal differentiation. Thus, Ngn2 leads to the maintenance of neural stem/progenitor cells by inducing Dll1 oscillation when its expression oscillates but to neuronal differentiation when its expression is sustained. These results indicate that the different dynamics of Hes1 and Ngn2 lead to different outcomes.